2015
DOI: 10.1016/j.ijcha.2014.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Poor R-wave progression and myocardial infarct size after anterior myocardial infarction in the coronary intervention era

Abstract: BackgroundRegeneration of R-wave or disappearance of Q-wave sometimes occurs after myocardial infarction (MI) especially in the coronary intervention era. We assessed the impact of poor R-wave progression (PRWP) or residual R-wave in precordial leads on myocardial infarct size in patients with prior anterior MI treated with coronary intervention.MethodsFifty-three patients with prior anterior MI and 20 age- and sex-matched patients without underwent electrocardiogram (ECG), myocardial perfusion single photon e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 17 publications
2
5
0
Order By: Relevance
“…2.2 2.1 3.9 7.7 3.7 5.1 1.9 1.9 0.9 1.0 0.9 0.9 0.9 0.9 0. duration: 124.1 ms and 107.7 ms (apical and inferolateral MI) vs. 90.4 ms (normal). PRWP mainly occurred in extensive anterior, septal, and apical MI, similar as reported in the literature [43], [45]. Specifically, the R wave amplitude in the septal MI was sometimes flattened, while the R wave of V6 tended to be larger than that of V5 in the apical MI, as Fig.…”
Section: B Sensitivity Analysis Of Qrs For Different Post-mi Characte...supporting
confidence: 86%
See 1 more Smart Citation
“…2.2 2.1 3.9 7.7 3.7 5.1 1.9 1.9 0.9 1.0 0.9 0.9 0.9 0.9 0. duration: 124.1 ms and 107.7 ms (apical and inferolateral MI) vs. 90.4 ms (normal). PRWP mainly occurred in extensive anterior, septal, and apical MI, similar as reported in the literature [43], [45]. Specifically, the R wave amplitude in the septal MI was sometimes flattened, while the R wave of V6 tended to be larger than that of V5 in the apical MI, as Fig.…”
Section: B Sensitivity Analysis Of Qrs For Different Post-mi Characte...supporting
confidence: 86%
“…To quantify discrepancy between QRS shapes, we employed a global measure, DTW, which compared signals of different lengths with an additional penalty for the difference in QRS duration between the two signals [18]. Furthermore, we introduced four QRS abnormalities reported in literature, i.e., QRS duration prolongation [41], pathological Q-waves [42], poor R wave progression (PRWP) [43], and fragmented QRS (fQRS) [44]. The reader is referred to Fig.…”
Section: B Sensitivity Analysis Of Qrs For Different Post-mi Characte...mentioning
confidence: 99%
“…For instance, poor R-wave progression (PRWP) is an important ECG finding that may be associated with many cardiac conditions, which have mortality implications for the medical director. PRWP refers to the failure to gradually increase for R wave toward V1 to V6 leads, which is commonly observed in the typical anterior myocardial infarction, LBBB, right, and left ventricular hypertrophy, Wolff-Parkinson-White syndrome and so on ( Mackenzie, 2005 ; Kurisu et al, 2015 ). A prospective cohort study of 5613 healthy population ( Anttila et al, 2010 ) suggested that PRWP was more frequent in women (7.0%) than that in men (2.7%) in three age groups 30 years or older.…”
Section: Discussionmentioning
confidence: 99%
“…After obtaining the cardiac cycles and key segments, we formulate rules for 15 ECG abnormalities according to criteria in the previous work [37], [40], [41]. The rules are somewhat simplified, but still maintain a high degree of consistency with experts' attention on ECGs.…”
Section: B Rule Inference Modulementioning
confidence: 99%
“…The formulas we use for identifying ECG abnormalities according to criteria in the medical literature [37], [40], [41]. t(s) indicates the duration of a segment s, computed according to Eq.…”
Section: Table Imentioning
confidence: 99%